(untitled) (Journal of the Bangladesh Agricultural University, 2014)
The present experiment was conducted to detect quality and level of the adulteration in milk collected from Dharchuni, Atani and Khamar bazar of Muktagacha Upazilla. Organoleptic parameters used to monitor the status of milk samples were color, flavor, taste, texture; physical parameter used was specific gravity; chemical parameters used were acidity, fat content, protein content, lactose content, ash, total solids, solids-not-fat; and the adulteration test used were starch test and formalin test. The tested milk samples showed significantly differences (p<0.05) for specific gravity, protein, fat, lactose and TS contents. No significant difference (p>0.05) were found for %acidity, ash content, and SNF content of milk samples. Milk collected from Khamar Bazar was higher for protein and fat contents than other markets. Adulteration tests, for all the samples were found negative. Although, there were some fluctuations among the parameters of milk samples regarding standard values; all of the milk samples were found to be acceptable. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18222 J. Bangladesh Agril. Univ. 11(1): 119-124, 2013